Perencanaan Loading Frame Menggunakan Material Baja Wind Cathcer Gedung A, Institut Teknologi Kalimantan - Hijriah, Hijriah; Akbar, Fachreza; Depari, Andi Sahputra; Gusti, Diony Septianugrah (Borneo Engineering : Jurnal Teknik Sipil, 2024)
The function of the wind catcher structure located in building A of Kalimantan Institute of Technology is no longer felt by building users. The construction causes leakage because it is located in the hallway of building A and is not covered by anything. This research was conducted to utilize and create a design of a fixed loading frame tool where the Integrated Laboratory 2 of the Kalimantan Institute of Technology requires the tool to support the research activities of students and outsiders. The method used in the research is the laboratory experimental method to determine the mechanical properties of the wind catcher structure steel material and the numerical method, namely ASD (Allowable Strength Design) to process, design and model the fixed loading frame tool. The results of the material tensile test test obtained a value of fy of 398 Mpa and fu of 514 Mpa, the dimensions of the frame are 4.55 x 2.95 m, the load model applied is one point and two point load. Modeling is done by trial and error load values and obtained load values in accordance with the capacity of the available profile frame, namely WF 300 x 150 x 6 x 9 can withstand loads of 200 kN and modeling in accordance with the design criteria load (1000 kN) the profile on the beam can be changed to WF 588 x 300 x 18 x 20 and on the column profile changed to WF 450 x 300 x 11 x 18.  The results of modeling a loading frame made of wind catcher structural profiles have met the design criteria parameters made by adding beams vertically in the x-axis beam (longitudinal) located at the center of the frame (vertical double beam design).